2001
DOI: 10.1007/s11627-001-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of embryogenic callus and cell suspension culture from shoot tips excised from flower stalk buds of Phalaenopsis (Orchidaceae)

Abstract: Embryogenic calluses were induced from 73% of Phalaenopsis shoot-tip explants excised from flower stalk buds by culturing for 7 mo. on New Dogashima Medium (NDM) containing 0.5 mM a-naphthaleneacetic acid (NAA), 4.4 mM 6-benzylaminopurine and 29.2 mM sucrose. The sucrose concentration was increased to 58.4 mM 4 mo. after initiation of the callus culture. These calluses were successfully subcultured as cell suspension cultures in liquid NDM supplemented with 5.4 mM NAA and 58.4 mM sucrose. By simply reducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 5 publications
1
40
0
9
Order By: Relevance
“…It is a natural growth promoter which contains higher levels of zeatin, zeatin ribosides, 1,3-diphenylurea (contains cytokinin like activity), auxins, nitrogenous compounds, inorganic elements, organic acids, sugars and their alcohols, peptides, vitamins, amino acids and many other unknown components in its composition (Tokuhara and Mii, 2001;Nasib et al, 2008). George et al, (2008) demonstrated that physiologically active substances presents in CW promote the cell divisions which further enhance shoot multiplication.…”
Section: Medium Supplementsmentioning
confidence: 99%
“…It is a natural growth promoter which contains higher levels of zeatin, zeatin ribosides, 1,3-diphenylurea (contains cytokinin like activity), auxins, nitrogenous compounds, inorganic elements, organic acids, sugars and their alcohols, peptides, vitamins, amino acids and many other unknown components in its composition (Tokuhara and Mii, 2001;Nasib et al, 2008). George et al, (2008) demonstrated that physiologically active substances presents in CW promote the cell divisions which further enhance shoot multiplication.…”
Section: Medium Supplementsmentioning
confidence: 99%
“…In most of plant species, regeneration of plants from callus tissue, especially highly totipotent embryogenic callus, has been recognized as one of the essential techniques for micropropagation and biotechnological applications (Tokuhara and Mii, 2001). Therefore, the interest in using these techniques for rapid and largescale propagation of medicinal and aromatic plants has been significantly increased (Sahoo et al, 1997;.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of plant growth regulators (PGRs) and sources of explants have been used to induce PLBs. PLB induction on MS medium with addition of BAP and NAA [7] or TDZ [4] using leaf explants from plantlets have been reported. The use of 5.4 µM NAA and 4.5 µM TDZ has been applied to induce PLBs and plantlets from flower stalks of Doritaenopsis orchids [8].…”
Section: Introductionmentioning
confidence: 99%